Pemberdayaan Lingkungan Melalui Pengadaan Sarana Prasarana di Desa Padang Makmur Bengkulu - Nadia Permata Sari; Ameliya Tantri; Sellia Yulan Fitri; Arina Sulastri; Sinria Oktama Putri; Yanto Effendi; Suwarni Suwarni; Liza Yulianti (Universitas Dehasen Bengkulu, 2026)
This community service activity was conducted in Padang Makmur Village, Betungan Urban Village, Bengkulu City, a densely populated area with a population of approximately 500 residents. The primary problems identified were the absence of regional identity in the form of street name signs, a lack of adequate waste disposal facilities, and minimal educational media regarding environmental cleanliness. These conditions made regional navigation difficult and led to unorganized household waste management. The objective of this service was to create a more organized, clean, and healthy environmental governance through the provision of basic infrastructure. The problem-solving method was carried out through three main stages: coordination with village officials, strategic location surveys, and physical implementation of the work programs. The results showed that the installation of street name signs facilitated regional identification and population administration. The provision of separated organic and non-organic trash bins in public areas, along with the installation of educational boards, successfully encouraged the community to begin sorting waste at the source. Through these steps, environmental issues in this area were resolved systematically, creating a more orderly, healthy, and sustainable village environment for the local community.